Film flowmeter automation process - Dilai, I. V.; Tepliukh, Z. M.; Hirniak, Yu. B. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The improved film flow meter with microprocessor control system to provide significant improvement of metrological and operating characteristics is suggested in the paper.